2020
DOI: 10.3390/su122410282
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Environmental Practices in Hospitality through Booking Websites and Online Tourist Reviews

Abstract: The major impact of hotel industry on the environment has become a serious concern for both hoteliers and tourists, with many studies showing that tourists are having more and more expectations from hoteliers to implement environmental practices. Considering the fact that most hotel bookings are now made online through booking websites, it is important for these to show and manifest the same preoccupation with the environment, by promoting environmentally friendly initiatives. The aim of the present study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The most highly challenging barrier to effective implementation of green practices was high maintenance costs (CV = 22.1). This is in agreement with the findings of Foris et al (2020) who stated that implementing environmentally sustainable practices brings new challenges like associated costs, although some new opportunities emerge. Dwivedi et al (2022) and Yusuf et al (2020) reported that one of the bottlenecks for effective implementation of green practices is high costs involved.…”
Section: Benefits Obtained By the Five-star Hoteliers As A Results Im...supporting
confidence: 92%
“…The most highly challenging barrier to effective implementation of green practices was high maintenance costs (CV = 22.1). This is in agreement with the findings of Foris et al (2020) who stated that implementing environmentally sustainable practices brings new challenges like associated costs, although some new opportunities emerge. Dwivedi et al (2022) and Yusuf et al (2020) reported that one of the bottlenecks for effective implementation of green practices is high costs involved.…”
Section: Benefits Obtained By the Five-star Hoteliers As A Results Im...supporting
confidence: 92%
“…The obtained results reveal that customer concerns about the environment and responsible consumption are a reality [4,28]. Hotel chains must not only develop actions and strategies aimed at preserving the environment but also must convert it into a corporate value.…”
Section: Discussionmentioning
confidence: 93%
“…The results showed that the relationship between the green image, satisfaction, trust, and behavioral intention in Generation Y are more significant than in the rest of the segments. Moreover, Foris et al [28] analyzed the environmental practices that hotels carry out on booking websites and how customers perceive them. The results indicated that the hotel sector needs to provide more information on environmental practices and better use different communication tools [19].…”
mentioning
confidence: 99%
“…This relevance of websites for marketing is also the case in the hospitality industry, due to the industry's ability to reach customers worldwide and address the needs of each target market [62]. Websites, and other digital platforms, have already been used for similar purposes by other researchers in the hospitality literature [36,57].…”
Section: Methodsmentioning
confidence: 96%
“…The green cause has also been seen as a marketing asset, resulting from the growth in the number of more informed consumers, impacting their purchasing decisions. Foris et al [36] stress that hotel customers are paying additional attention to sustainability issues, and therefore a growing number of hotels are communicating these practices, namely through social media. However, those authors also stress the need for hotel companies to improve their communication efforts, namely in booking platforms.…”
Section: Environmental Sustainability and The Hotel Industrymentioning
confidence: 99%